Allopurinol treatment adversely impacts left ventricular mass regression in patients with well-controlled hypertension. Issue 12 (December 2019) - Gingles, Christopher R.; Symon, Ruth; Gandy, Stephen J.; Struthers, Allan D.; Houston, Graeme; MacDonald, Thomas M.; Lang, Chim C.; Donnan, Peter T.; George, Jacob
Abstract : Objectives: Previous studies have demonstrated that high-dose allopurinol is able to regress left ventricular (LV) mass in cohorts with established cardiovascular disease. The aim of this study was to assess whether treatment with high-dose allopurinol would regress LV mass in a cohort with essential hypertension, LV hypertrophy and well-controlled blood pressure but without established cardiovascular disease. Methods: We conducted a mechanistic proof-of-concept randomized, placebo-controlled, double-blind trial of allopurinol (600 mg/day) versus placebo on LV mass regression. Duration of treatment was 12 months. LV mass regression was assessed by Cardiac Magnetic Resonance. Secondary outcomes were changes in endothelial function (flow-mediated dilatation), arterial stiffness (pulse wave velocity) and biomarkers of oxidative stress. Results: Seventy-two patients were randomized into the trial. Mean baseline urate was 362.2 ± 96.7 μmol/l. Despite good blood pressure control, LV mass regression was significantly reduced in the allopurinol cohort compared with placebo (LV mass −0.37 ± 6.08 versus −3.75 ± 3.89 g; P  = 0.012). Oxidative stress markers (thiobarbituric acid reactive substances) were significantly higher in the allopurinol group versus placebo (0.26 ± 0.85 versus −0.34 ± 0.83 μmol/l; P  = 0.007). Other markers of vascular function were not significantly different between the two groups. Conclusion: Treatment with high-dose allopurinol in normouricemic controlled hypertensive patients and LV hypertrophy is detrimental. It results in reduced LV mass regression and increased oxidative stress over a 12-month period. This may be because of an adverse impact on redox balance. Cohort selection for future cardiovascular trials with allopurinol is crucial.